Draft Genome Sequence of Lactobacillus gasseri Strain 2016 - Karlyshev, Andrey V. (American Society for Microbiology, 2013)
Different common factors contribute to the antagonistic properties of Lactobacillus gasseri toward various pathogens. However, there is strain-to-strain variation in the probiotic properties of this bacterium. The draft genome sequence of L. gasseri strain 2016 determined in this study will assist in understanding the genetic basis for such variation.